Korpus slovenske arhitekture 2003 - Fister, Peter (AR. Arhitektura, raziskave, 2004)
Long-term research project about architecture in Slovenia and establishment of a fundamental database: a comprehensive corpus (archive "Corpus of Slovene architecture"). Research is done by third and fourth year graduate students of architecture as Studio work and within the framework of the subject Development of architecture and Rehabilitation, by post-graduate students in selected subjects or as masters and doctorate themes, as well as selected associates from institutions that are involved with similar themes. In 2003 cooperation was enhanced on the national and especially international level (groups of professors and students from USA, Germany and Italy).
Keywords: architecture; arhitektura; raziskovalno delo; arhitekturna dediščina; stavbna dediščina; raziskave; Slovenia; Slovenija